Calculus 10th Edition

Published by Brooks Cole
ISBN 10: 1-28505-709-0
ISBN 13: 978-1-28505-709-5

Chapter 2 - Differentiation - 2.3 Exercises: 126

Answer

$-12-x(12x)-2(66x^2-6)$ $=(12-12)+(-12x^2-12x^2)$ $=-24x^2.$

Work Step by Step

Using the Power Rule: $y'=6x^2-6.$ Using the Power Rule: $y''=\dfrac{d}{dx}y'=12x.$ Using the Power Rule: $y'''=\dfrac{d}{dx}y''=12.$ $-12-x(12x)-2(66x^2-6)$ $=(12-12)+(-12x^2-12x^2)$ $=-24x^2.$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.